Adaptation of Trauma-Focused Cognitive Behavioural Therapy for cases of child sexual abuse with complex trauma: A clinical case illustration - Hébert, Martine; Daignault, Isabelle V.; Blanchard-Dallaire, Claudia (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2020)
Child sexual abuse is an important public health issue given its magnitude and the multiple associated consequences. The diversity of profiles in child victims of sexual abuse calls for a more personalized approach to treatment. Indeed, recent studies suggest that children display a variety of symptoms and that a subgroup of sexually abused children may present a profile of complex trauma. This article first presents a review of the scientific literature that positions Trauma-Focused Cognitive Behavioural Therapy (TF-CBT; Cohen et al., 2017) amongst the best practices to address trauma-related symptoms following child sexual abuse; whether it is co-occurring with other forms of violence or not. Various adaptations of TF-CBT therapy are proposed by the authors (Cohen et al., 2012) to treat children facing complex trauma. These adaptations are summarized and illustrated with the presentation of a clinical case involving two siblings from the same family.